A multiscale magneto-thermo-mechanically coupled model for ultra-low-field induced magneto-elastocaloric effect in magnetostrictive-shape memory alloy composite system. (1st November 2021) - Yu, Chao; Kang, Guozheng
Abstract: Recent experimental results show that apparent magneto-elastocaloric effect can be induced in the magnetostrictive-shape memory alloy composite system under an ultra-low magnetic field. In this paper, a multiscale theoretical model is constructed to predict the magneto-thermo-mechanically coupled response of such a composite system by considering the multi-field interactions among the heterogeneous constituent elements in the grain, polycrystalline aggregate and macroscopic scales. In the grain scale, for the magnetostrictive alloy (MEA), the fluctuations of stress and magnetic fields caused by the interactions among the domains are addressed by the self-consistent homogenization scheme. Adopting a probabilistic domain switching criterion based energetic analysis, a constitutive model of MEA is established. For the shape memory alloy (SMA), a crystal plasticity based thermo-mechanically coupled constitutive model is constructed in the framework of irreversible thermodynamics. The interactions among austenite phase and martensite variants are considered by the Mori-Tanaka's homogenization scheme. Thermodynamic driving force for martensite transformation and the internal heat production originated from transformation latent heat and inelastic deformation dissipation are derived from the dissipative inequality and the conservation of energy, respectively. In the polycrystalline aggregate scale, to estimate the interactions among the grains and predict the overall responses of the polycrystalline aggregates of MEA and SMA, a unified incremental magneto-thermo-mechanically coupled self-consistent homogenization scheme is developed. In the macroscopic scale, the magneto-thermo-mechanical interaction equations among the MEA rod, SMA cuboid and Al alloy frame in the composite system are derived by considering the conditions of deformation compatibility, force balance and thermodynamic equilibrium. The capability of the proposed multiscale model to describe the magneto-elastocaloric effect of MEA-SMA composite system is validated by comparing the predictions with the existing experimental data. Moreover, the influences of geometric dimension, pre-load, frame's stiffness and crystallographic orientation on the magneto-elastocaloric effect of the composite system are discussed. The proposed model provides a theoretical guidance for the optimization design of solid-state refrigeration devices in both the microscopic and macroscopic scales.